Nicolás de Piérola and the articulation with his agents in Europe and Central America during the War of the Pacific (1881-1883) - Abanto Chani, Julio (2021)
One of the main gaps in Peruvian historiography on the Pacific War is to reconstruct the steps taken by Nicolás de Piérola in Europe (1882-1884), after facing various scenarios such as the fall of Lima, losing the Presidency of the Republic in November 1881 and founding the short-lived National Party. When Piérola left for France (March 1882) he adopted a position of abstention and did not get involved in the war. Since that time, no further information is available on its operations abroad. Therefore, thanks to the information from the Piérola Archive of the National Library of Peru, the reconstruction of Piérola’s relations between 1881 and 1883 will be carried out with his main collaborators located in three key countries for the course of the war: France (the diplomat Toribio Sanz), England (Admiral Aurelio García y García) and Panama (Colonel and Consul General Federico Larrañaga).